Critical Nurse Performance Based on Training and Work Motivation - Nurpratomo, Ari; Gemina, Dwi; Samsuri (International Journal of Managemen Analytics (IJMA), 2024)
This research aims to determine the effect of training and work motivation on the performance of critical care nurses at Dr. Lung Hospital. M. Goenawan Partowidigdo Cisarua Bogor. The sample in this study was 85 people. The results of the validity and reliability tests show that all question items are declared valid and reliable. The research method uses multiple linear regression with IBM SPSS software. The multiple regression analysis of the F test (simultaneous) states that there is a simultaneous positive and significant influence between training and work motivation on the performance of critical nurses. The results of the t-test (partial) stated that training had a positive and significant effect on the performance of critical nurses and work motivation had a positive and significant effect on the performance of critical nurses at Dr. Lung Hospital. M. Goenawan Partowidigdo Cisarua Bogor.